2021
DOI: 10.3233/ves-201539
|View full text |Cite
|
Sign up to set email alerts
|

Visual-vestibular mismatch correlates with headache

Abstract: BACKGROUND: Dizziness affects 20–30%of the general population. A subgroup of dizzy patients with chronic migraine suffers vertigo implying that the migraine has a vestibular component. Vestibular migraine remains a diagnosis of exclusion based on history. OBJECTIVE: A link between headaches and dizziness suggests that these individuals would demonstrate dizziness and instability in complex, dynamic visual environments as a result of an inability to correctly process conflicting visual and vestibular signals. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In VM patients, our results indicate that the %CA was normal in most of the subjects, and only when using the optokinetic stimulation did this parameter strongly decrease (with no difference between the two sides) not only with respect to the control group but also in comparison with the AUV group, showing that visual dependence is the cause of the decay in the responses when the background is in motion. Recently, Al-Sharif et al [32] studied the effects of visual-vestibular mismatch using a specific questionnaire and a computerized rod and frame test; they reported that the presence of VD was significantly higher in patients suffering from headache and dizziness than in subjects with headache only. Visual dependence was measured as the error to a subjective visual vertical using a computerized rod and frame test.…”
Section: Discussionmentioning
confidence: 99%
“…In VM patients, our results indicate that the %CA was normal in most of the subjects, and only when using the optokinetic stimulation did this parameter strongly decrease (with no difference between the two sides) not only with respect to the control group but also in comparison with the AUV group, showing that visual dependence is the cause of the decay in the responses when the background is in motion. Recently, Al-Sharif et al [32] studied the effects of visual-vestibular mismatch using a specific questionnaire and a computerized rod and frame test; they reported that the presence of VD was significantly higher in patients suffering from headache and dizziness than in subjects with headache only. Visual dependence was measured as the error to a subjective visual vertical using a computerized rod and frame test.…”
Section: Discussionmentioning
confidence: 99%
“…In VM patients our results indicate that the %CA is normal in most of the subjects and only using the optokinetic stimulation this parameter strongly decrease (with no difference between the two sides) in respect not only to the control group but also in comparison with the AUV group showing that visual dependence is the cause of the decay of the responses when the background is in motion. Recently, Al-Sharif et al [30] studied the effects of visual-vestibular mismatch using a speci c questionnaire and a computerized Rod and Frame test; they reported that the presence of VD is signi cantly higher in patients suffering from headache and dizziness than in subjects with headache only. Our results are in line with this observation indicating a very important role of the vestibular involvement in VM causing a di culty in resolving con icting visuo-vestibular signals, as demonstrated by the signi cant difference in delta CS between our three group of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of visual dependency was confirmed with a Rod and Frame test (RFT) available on the PosturoVR 0.8.3 software (Virtualis, France) and projected on to the Oculus Rift [8]. At the beginning of each trial, the virtual rod was set randomly at a 45 deg angle to the left or right.…”
Section: Self-reported Outcomes Measuresmentioning
confidence: 99%
“…Differences in demographics and clinical outcome scores between the + VVM and −VVM groups were assessed using Welch's t-test. Individuals were assigned positive or negative results on the RFT based on the criterion of an angle of deviation greater than 5 deg to indicate visual dependency [8].…”
Section: Postural Acceleration Measuresmentioning
confidence: 99%
See 1 more Smart Citation